A study of the contribution of variables related to companion animals on positivity - Dieker Larson, Erica Dawn (Kansas State University, 2015)
The broaden-and-build theory posits that frequently experiencing positive emotions leads to broadened awareness and functioning, and over time, built resources. These resources function as reserves during difficult times. Considering recommendations for increasing positive emotions and findings regarding human-animal interactions, it is reasonable to expect that companion animals might function in a manner to increase positive emotions. Many people have companion animals, and they are a preventative, natural intervention without associated stigmas. Therefore, knowing more about how companion animals impact their humans has practical implications for mental health professionals. The current study investigated various aspects of human-animal interactions that are conceivably related to positive emotions (human-animal bond and amount of time spent with animal) in different configurations (people with and without companion animals; people with dogs, cats, and horses), while considering potential confounds (time spent with humans in connected interactions and time spent outside). Time spent in connected interactions with other humans is the only variable that predicted positivity, and this was only in people without companion animals. This is consistent with previous findings that interacting with other people is related to positive emotions.
Keywords: Positive Emotions; Broaden and Build Theory; Companion Animals; Counseling Psychology (0603)